Pengaruh Individual Caracteristic Job Crafting Terhadap Employe Performance Melalui Job Satisfaction - Hardiyanti, Siti Namira; Siswadi, Yudi (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2023)
AbstractThe aims of this study are to explore the mediating impact of job satisfaction on job skills, characteristics and employee performance. Methodological design of a questionnaire answered by 157 employees working at PT. Mighty harvest facility with SEM PLS data analysis. The research results show that the relationship between individual characteristics and employee performance is positive and significant. The relationship between individual characteristics and job satisfaction shows that it is significantly positive. Job crafting on employee performance is negative, indicating that the relationship between crafting and employee performance has a small influence. There is a positive and significant relationship between job crafting and job satisfaction. Job satisfaction with employee performance shows that it has a significant positive relationship. Practical implications Companies can shape organizational culture and increase employee job satisfaction in general. Furthermore, this research enriches the organizational behavior literature by recognizing and empirically validating the role of individual characteristics, employee involvement in improving performance. The originality of the findings of this research can help in creating a better understanding of job satisfaction and describe its relationship with leadership character.Keywords: Individual Characteristics, Job Crafting, Job Satisfaction, Employee Performance.Abstrak Tujuan - tujuan dari study ini adalah untuk mengeksplorasi dampak mediasi kepusan kerja terhadap kerajinan kerja, caracteristik, kinerja karyawan. Desain metodologi sebuah kuesioner dijawab oleh 157 karyawan yang bekerja di PT. sarana panen perkasa dengan analisis data SEM PLS. Hasil penelitian menunjukkan bahwa adanya hubungan antara individual caracteristic dan employee performance positif dan signifikan. Adanya hubungan Individual caracteristic terhadap job satisfaction menunjukkan bahwa positif signifikan. Job crafting terhadap employe performance artinya negatif yang menunjukkan bahwa hubungan antara crafting dan employee performance memiliki pengaruh kecil. Adanya hubungan Job crafting terhadap job satisfaction yang positif dan signifikan. Job satisfaction terhadap employee performance menunjukkan bahwa memiliki hubungan positif signifikan. Implikasi praktis Perusahaan dapat membentuk budaya organisasi dan meningkatkan kepuasan kerja karyawannya secara umum. Lebih lanjut, penelitian ini memperkaya literatur perilaku organisasi dengan mengenali dan memvalidasi secara empiris peran individual caracteristic, keterlibatan karyawan dalam meningkatkan kinerja. Orisinalitas temuan penelitian ini dapat membantu dalam menciptakan pemahaman yang lebih baik tentang kepuasan kerja dan menggambarkan hubungannya dengan karakterkepemimpinan.Kata Kunci: Individual Karakteristik, Job Crafting, Job Satisfaction, Employe Performance.